2005
DOI: 10.1677/jme.1.01857
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of cDNAs encoding steroidogenic acute regulatory protein from freshwater stingrays (Potamotrygon spp.)

Abstract: The steroidogenic acute regulatory protein (StAR) is critical to the regulated synthesis of steroids in vertebrates. We have isolated cDNA sequences encoding StAR in the freshwater stingrays Potamotrygon hystrix and P. motoro. A single P. hystrix StAR transcript (3376 bp) and two overlapping P. motoro StAR transcripts (1272 and 3365 bp) were isolated. The P. hystrix and P. motoro StAR transcripts contain open reading frames encoding proteins of 284 amino acids that are 99% identical to each other and 56-64% id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…This finding is in agreement with previous data in several fish species where StAR is mainly expressed in the steroidogenic tissues (Bauer et al 2000, Li et al 2003, Goetz et al 2004, although it is in contraposition to the results obtained in other species, where StAR mRNA expression has been described in extragonadal and extra-adrenocortical tissues, such as the brain and heart of the freshwater stingray (Nunez et al 2005); the kidney of Atlantic croacker (Nunez & Evans 2007); the intestine, pyloric ceca, spleen, and kidney of trout (Kusakabe et al 2002); human fetal and adult kidney (Sugawara et al 1995); and several areas of the human brain (King et al 2002). Therefore, StAR tissue distribution can be slightly different according to the species, and its role in these other tissues remains to be clarified.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with previous data in several fish species where StAR is mainly expressed in the steroidogenic tissues (Bauer et al 2000, Li et al 2003, Goetz et al 2004, although it is in contraposition to the results obtained in other species, where StAR mRNA expression has been described in extragonadal and extra-adrenocortical tissues, such as the brain and heart of the freshwater stingray (Nunez et al 2005); the kidney of Atlantic croacker (Nunez & Evans 2007); the intestine, pyloric ceca, spleen, and kidney of trout (Kusakabe et al 2002); human fetal and adult kidney (Sugawara et al 1995); and several areas of the human brain (King et al 2002). Therefore, StAR tissue distribution can be slightly different according to the species, and its role in these other tissues remains to be clarified.…”
Section: Discussionsupporting
confidence: 92%
“…However, in freshwater stingrays (Potamotrygon spp. ), StAR mRNA is expressed in several tissues such as the atria, ventricle, gill, interrenal gland and muscle, suggesting that StAR may be critical to processes other than steroidogenesis [57].…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of standard steroids injected per 20 ll (a, c) were cortisol-7.24 ng, 21-deoxycortisol-6.92 ng, corticosterone-6.93 ng, deoxycorticosterone-6.60 ng, testosterone-5.76 ng, 17-P-6.92 ng, 17,20b-DP-6.65 ng, and P 4 -6.39 ng et al (2003) demonstrated the expression of P450 C17 in the brain of fathead minnow Pimephales promelas. Nunez et al (2005) have cloned and characterized cDNA encoding StAR from freshwater stingrays Potamotrygon hystrix and P. motoro. Thus, our present data and various studies in other fish groups strongly suggest that neurosteroid biosynthesis occurs in the brain of fishes, as has been previously shown for amphibians, birds, and mammals (Do Rego et al 2009).…”
Section: Discussionmentioning
confidence: 99%